Designing Business Development Strategies for XYZ Subsidized Housing Developers in East Java With QSPM - Rahma Fariza; Eric Harianto (Eduvest - Journal of Universal Studies, 2025)
This study formulates a corporate development plan for XYZ Housing Developer using Management Strategy Theory and the Quantitative Strategic Planning Matrix (QSPM). The objective is to leverage XYZ's unique resources and capabilities to secure a sustainable competitive advantage in the housing industry. The research begins with an analysis of Management Strategy Theory, emphasizing its importance in strategic management. It identifies XYZ's strategic resources, which are crucial for enhancing its market position. QSPM is applied to evaluate and prioritize strategic alternatives based on internal resources and external conditions. The findings highlight that strategies focusing on sustainable construction and customer relationship management are particularly advantageous. Data triangulation through multiple validation methods—expert reviews, stakeholder interviews, and empirical analysis—ensures research reliability and validity. Results show a strong correlation between effective resource utilization and improved business performance, including higher customer satisfaction and market share. This research contributes to the field by showcasing the application of Management Strategy in the housing sector and the effectiveness of QSPM in guiding strategic decisions. The study provides valuable insights for developing sustainable strategies in a competitive market.